Biocatalytic "Oxygen‐Fueled" Atom Transfer Radical Polymerization. (8th November 2018) - Enciso, Alan E.; Fu, Liye; Lathwal, Sushil; Olszewski, Mateusz; Wang, Zhenhua; Das, Subha R.; Russell, Alan J.; Matyjaszewski, Krzysztof
Abstract: Atom transfer radical polymerization (ATRP) can be carried out in a flask completely open to air using a biocatalytic system composed of glucose oxidase (GOx) and horseradish peroxidase (HRP) with an active copper catalyst complex. Nanomolar concentrations of the enzymes and ppm amounts of Cu provided excellent control over the polymerization of oligo(ethylene oxide) methyl ether methacrylate (OEOMA500 ), generating polymers with high molecular weight ( M n >70 000) and low dispersities (1.13≤ Đ ≤1.27) in less than an hour. The continuous oxygen supply was necessary for the generation of radicals and polymer chain growth as demonstrated by temporal control and by inducing hypoxic conditions. In addition, the enzymatic cascade polymerization triggered by oxygen was used for a protein and DNA functionalized with initiators to form protein‐ b ‐POEOMA and DNA‐ b ‐POEOMA bioconjugates, respectively.